2021
DOI: 10.1155/2021/6618874
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Probiotic or Synbiotic Supplementation Modulates Jejunal and Colonic Antioxidant Capacity, Mitochondrial Function, and Microbial Abundance in Bama Mini‐piglets

Abstract: The present study was conducted to investigate the effects of maternal probiotic or synbiotic supplementation during gestation and lactation on antioxidant capacity, mitochondrial function, and intestinal microbiota abundance in offspring weaned piglets. A total of 64 pregnant Bama mini-sows were randomly allocated into the control group (basal diet), antibiotic group ( basal   diet + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 59 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…The real-time PCR conditions were as follows: an initial step at 95 • C for 5 min, followed by 40 cycles of denaturation at 95 • C for 5 s, annealing at 60 • C for 30 s, and a final extension at 72 • C for 30 s. Pig-specific primer sequences are shown in Supplementary Table 2 (Sangon Biotech, Shanghai, China). Target gene expression was calculated using the 2 − Ct value (19), and β-actin was used as the internal control.…”
Section: Rna Isolation and Real-time Quantitative Pcr Analysismentioning
confidence: 99%
“…The real-time PCR conditions were as follows: an initial step at 95 • C for 5 min, followed by 40 cycles of denaturation at 95 • C for 5 s, annealing at 60 • C for 30 s, and a final extension at 72 • C for 30 s. Pig-specific primer sequences are shown in Supplementary Table 2 (Sangon Biotech, Shanghai, China). Target gene expression was calculated using the 2 − Ct value (19), and β-actin was used as the internal control.…”
Section: Rna Isolation and Real-time Quantitative Pcr Analysismentioning
confidence: 99%
“…Previous studies have found that dietary betaine addition during the growing and finishing stages improved the growth performance and meat quality of animals ( 21 , 22 ). In addition, maternal nutrition also influences the offspring's growth later in life ( 23 ). Therefore, the present study evaluated the effects of betaine addition in sow and sow-offspring diets on the growth performance and meat quality-associated parameters of pigs at different stages.…”
Section: Discussionmentioning
confidence: 99%
“…In the excreta of broilers, synbiotics increased the concentrations of lactic acid and short chain fatty acid (SCFA), while decreasing the concentration of branched chain fatty acid (BCFA). These findings revealed that the studied synbiotics had a positive impact on the intestinal microbiota, metabolism, and broiler chicken performance [ 152 ].…”
Section: Applications To Animal Healthmentioning
confidence: 99%